Meeting society's transport needs under tight budgets - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
In the aftermath of the 2008 financial crisis, both the private and public sectors face stringent constraints in funding for transport infrastructure investment and transport services. At the same time, economic recession highlights the social value of public support for disadvantaged users of transport services and more generally the importance of effective transport systems to efficient labour markets and access to jobs. This drives governments to focus anew on efficiency in the delivery of transport services and infrastructure investments and on efficient targeting of support for public transport. In developing economies these policy concerns are amplified by rapid urbanisation, which makes coordination of transport services across metropolitan areas imperative.
Keywords: 330